Christmas in Camelot - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2001)
On Christmas Eve, Jack and Annie$1 (Bs tree house transports them to King Arthur$1 (Bs castle at Camelot, where they undertake a quest to the castle of the Otherworld.s
Keywords: Camelot (Legendary place) -- Fiction; Time travel -- Fiction; Magic -- Fiction; Christmas -- Fiction; Tree houses -- Fiction; Brothers and sisters -- Fiction